Drought-Induced Zinc Finger Transcription Factor OsDi19-3 Positively Regulates Drought Stress Acclimatization in Rice (Oryza sativa L.) - Yanjie Li; Tianjiao Mu; Tianying Ren; Pan Li (Plants)
The plant Di19 (drought-induced 19) protein belongs to zinc finger transcription factors, which play crucial roles in drought stress acclimatization. OsDi19-3, a drought-induced transcription factor in rice, has not been fully characterized for its biological role in stress acclimatization. In this study, transgenic rice overexpressing OsDi19-3 was generated. Water deprivation experiments showed that transgenic plants exhibited higher drought tolerance than wild-type (WT) plants, indicating that OsDi19-3 positively regulates drought stress acclimatization. Consistent with this, stomata in overexpression lines closed more significantly than those in WT under drought stress. To explore the molecular mechanism, yeast two-hybrid and bimolecular fluorescence complementation (BiFC) experiments identified two interacting proteins of OsDi19-3: OsCAMK1 and OsNEK6. Notably, these two proteins also interacted with each other. A transcriptome analysis of OsDi19-3 transgenic plants revealed 224 upregulated and 167 downregulated genes (log2(OE/WT) > 1, p-value < 0.05), including multiple stress-responsive genes. Furthermore, a ChIP-PCR analysis confirmed that OsDi19-3 directly binds to three target genes. This study provides insights into the role of OsDi19-3 in drought acclimatization and its regulatory network in rice.